All-solid-state secondary battery and method for manufacturing same
By using a protective member including a multi-layer thermoplastic resin layer in an all-solid secondary battery, the problem of rupture of the solid electrolyte layer in the temperature and pressure process is solved, and the reliability and durability of the battery are improved.
Patent Information
- Application Number
- CN202410729829.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-18
- Filing Date
- 2024-06-06
- Publication Date
- 2025-04-18
AI Technical Summary
When performing the temperature-pressure process, the stress difference caused by the area difference between the negative electrode layer, the positive electrode layer and the solid electrolyte layer in an all-solid secondary battery may cause the solid electrolyte layer to rupture, reducing the reliability of the battery.
These layers are arranged in sequence by stacking and providing the peripheral portion of the unprotected positive electrode layer of the solid electrolyte layer to compensate for the area difference between the positive electrode layer and the solid electrolyte layer by compensating the area difference between the positive electrode layer and the solid electrolyte layer.
Through the use of protective components, the risk of solid electrolyte layer breaking due to stress differences in the temperature and pressure process is reduced, and the reliability and durability of all-solid secondary batteries are improved.
Smart Images

Figure CN119852469A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority from Korean Patent Application No. 10-2023-0139656 filed on October 18, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present disclosure relates to an all-solid-state secondary battery and a method for manufacturing the same. Background Art
[0004] Generally, an all-solid-state secondary battery can be provided in the form of a unit cell, which includes a negative electrode (anode) layer, a positive electrode (cathode) layer, and a solid electrolyte layer between the negative electrode layer and the positive electrode layer. For example, the all-solid-state secondary battery can include a battery stack, which includes a stacked structure of multiple unit cells.
[0005] In order to form the above-mentioned battery stack, a warm pressing process is generally used to stack a plurality of unit cells and press the final structure in the stacking direction. In this case, a warm pressing (e.g., warm isostatic pressing) process may be performed to bond the solid electrolyte layer to the negative electrode layer and / or the positive electrode layer by sintering, and the warm pressing process is a process of pressing a plurality of stacked unit cells in the stacking direction at a relatively high temperature (e.g., 90°C).
[0006] In some cases, when the above-mentioned warm pressing process is performed, the solid electrolyte layer may be broken due to the stress difference generated by the area difference between the negative electrode layer, the positive electrode layer and / or the solid electrolyte layer included in the unit cell (for example, the positive electrode layer has a smaller area). Therefore, the reliability of the all-solid-state secondary battery may be reduced. Summary of the invention
[0007] The present disclosure aims to solve the above-mentioned problems occurring in the prior art while maintaining the advantages achieved by the prior art.
[0008] An aspect of the present disclosure provides an all-solid-state secondary battery having improved reliability and a method of manufacturing the all-solid-state secondary battery having improved reliability.
[0009] The technical problems to be solved by the present disclosure are not limited to the above-mentioned problems, and those skilled in the art to which the present disclosure belongs will clearly understand any other technical problems not mentioned herein through the following description.
[0010] According to one aspect of the present disclosure, an all-solid-state secondary battery may include: a battery stack having a stacking structure formed by stacking a plurality of unit cells, each unit cell including: a negative electrode layer; a pair of solid electrolyte layers, the negative electrode layer being interposed between the solid electrolyte layers; and a positive electrode layer, the area of the positive electrode layer facing one solid electrolyte layer being smaller than the area of the negative electrode layer facing one solid electrolyte layer, the positive electrode layer being arranged opposite to the negative electrode layer so that one solid electrolyte layer from among the solid electrolyte layers is interposed between the negative electrode layer and the positive electrode layer; and a protective member including a first thermoplastic resin layer, a second thermoplastic resin layer, and a third thermoplastic resin layer, the first thermoplastic resin layer, the second thermoplastic resin layer, and the third thermoplastic resin layer being sequentially stacked and arranged on a peripheral portion of the solid electrolyte layer where the positive electrode layer is not arranged while being interposed between two solid electrolyte layers arranged adjacent to each other so that the positive electrode layer is interposed therebetween. The glass transition temperature of the first thermoplastic resin layer and the glass transition temperature of the third thermoplastic resin layer are lower than the glass transition temperature of the second thermoplastic resin layer.
[0011] According to another aspect of the present disclosure, a method for manufacturing an all-solid-state secondary battery may include: forming a primary battery stack formed by stacking a plurality of unit cells, each unit cell may include: a negative electrode layer; a pair of solid electrolyte layers, the negative electrode layer being interposed between the solid electrolyte layers; and a positive electrode layer, arranged opposite to the negative electrode layer, such that one solid electrolyte layer from among the solid electrolyte layers is interposed between the negative electrode layer and the positive electrode layer, and an area of the positive electrode layer facing one solid electrolyte layer is smaller than an area of the negative electrode layer facing one solid electrolyte layer, and a protective member may be arranged in the unit cell, the protective member including a first thermoplastic resin layer, a second thermoplastic resin layer and a third thermoplastic resin layer, the first thermoplastic resin layer, the second thermoplastic resin layer and the third thermoplastic resin layer being stacked sequentially in a peripheral portion of a solid electrolyte layer where the positive electrode layer is not arranged and on a side surface of the positive electrode layer; and forming a battery stack by performing a warm pressing process on the primary battery stack in a stacking direction in which the plurality of unit cells are stacked, the glass transition temperature of the first thermoplastic resin layer and the glass transition temperature of the third thermoplastic resin layer may be lower than the glass transition temperature of the second thermoplastic resin layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The above and other objects, features and advantages of the present disclosure will become more apparent from the following detailed description taken in conjunction with the accompanying drawings:
[0013] Figure 1 is a view showing an example all-solid-state secondary battery according to an embodiment of the present disclosure;
[0014] Figure 2 It is shown Figure 1 An enlarged view of area A;
[0015] Figure 3is a view showing an example manufacturing method of an all-solid-state secondary battery according to an embodiment of the present disclosure;
[0016] Figure 4 Show Figure 3 an enlarged view of region B and region B';
[0017] Figure 5 is an optical microscope (OM) image of an example all-solid-state secondary battery manufactured according to an embodiment of the present disclosure;
[0018] Figure 6 is an optical microscope (OM) image of an example all-solid-state secondary battery manufactured according to a comparative example of the present disclosure;
[0019] Figure 7 is a graph showing evaluation of capacity retention characteristics of an all-solid-state secondary battery manufactured according to an example embodiment of the present disclosure; and
[0020] Figure 8 is a graph showing evaluation of output characteristics of an all-solid-state secondary battery manufactured according to an example embodiment of the present disclosure.
[0021] Reference numerals
[0022] ST: Battery stack ST 0 :Primary battery stack
[0023] 10: Negative electrode layer 11: Negative electrode current collector layer
[0024] 12, 13: Negative electrode active material layer 20: Positive electrode layer
[0025] 21: Positive electrode current collector layer 22, 23: Positive electrode active material layer
[0026] 30: A pair of solid electrolyte layers (31, 32) UC: Unit cell
[0027] L1: First layer L2: Second layer
[0028] L3: The third layer 40: protection components
[0029] 41: first thermoplastic resin layer 42: second thermoplastic resin layer
[0030] 43: Third thermoplastic resin layer DETAILED DESCRIPTION
[0031] Hereinafter, an all-solid-state secondary battery and a method of manufacturing the same will be described in detail so that those skilled in the art can easily reproduce the present disclosure.
[0032] All-solid-state secondary battery
[0033] Figure 1 is a view showing an all-solid-state secondary battery according to an embodiment of the present disclosure.
[0034] Reference Figure 1 According to the present disclosure, the all-solid secondary battery may include a battery stack ST having a stack structure in which a plurality of unit cells UC are stacked and a protective member 40. The unit cell UC may include a negative electrode layer 10, a pair of solid electrolyte layers 30, and a positive electrode layer 20.
[0035] Although, for ease of description, Figure 1 The first layer L1, the second layer L2, and the third layer L3 defined by the stacked three unit cells UC are shown, but the present disclosure is not limited thereto. For example, the battery stack ST may have a four-layer structure, a five-layer structure, or a stacked structure having five or more layers.
[0036] The negative electrode layer 10 may include a negative electrode active material layer and / or a negative electrode current collector layer. In this case, the negative electrode active material layer and the negative electrode current collector layer may adopt various types of negative electrode active material layers and various types of negative electrode current collector layers that are well known and commonly used in the negative electrode layer 10 of an all-solid-state secondary battery, but are not limited thereto.
[0037] The negative electrode layer 10 may be interposed between a pair of solid electrolyte layers 30. In other words, Figure 1 As shown, the pair of solid electrolyte layers 30 may include a solid electrolyte layer 31 disposed on the bottom surface of the negative electrode layer 10 and a solid electrolyte layer 32 disposed on the top surface of the negative electrode layer 10 .
[0038] The solid electrolyte included in the solid electrolyte layer 30 may adopt various types of solid electrolytes generally used in all-solid-state secondary batteries, but is not limited thereto. For example, a pair of solid electrolyte layers 30 may include at least one selected from the group consisting of a polymer solid electrolyte, a sulfide solid electrolyte, and an oxide solid electrolyte.
[0039] The positive electrode layer 20 may include a positive electrode active material layer and / or a positive electrode current collector layer. In this case, the positive electrode active material layer and / or the positive electrode current collector layer may adopt various types of positive electrode active material layers and various types of positive electrode current collector layers that are commonly used in all-solid-state secondary batteries and are well known, but are not limited thereto.
[0040] The positive electrode layer 20 may be disposed opposite to the negative electrode layer 10 so that the solid electrolyte layer 32 is interposed between the positive electrode layer 20 and the negative electrode layer 10. In this case, the area of the positive electrode layer 20 facing the solid electrolyte layer 32 may be smaller than the area of the negative electrode layer 10 facing the solid electrolyte layer 32. This is because the capacity characteristics of the all-solid-state secondary battery are determined by the positive electrode layer 20. When the area of the positive electrode layer 20 is used as effectively as possible, the capacity characteristics of the all-solid-state secondary battery can be improved.
[0041] In some cases, as described above, since the areas of the negative electrode layer 10 and the solid electrolyte layer 30 are larger than the areas of the positive electrode layer 20, the negative electrode layer 10 and the solid electrolyte layer 30 in the stacked battery ST may have side surfaces protruding from the side surfaces of the positive electrode layer 20, such as Figure 1 In this case, when pressure is applied in the stacking direction of the unit cells UC, the solid electrolyte layer 30 may be broken due to a stress difference generated by the area difference between the positive electrode layer 20 and the solid electrolyte layer 30 (for example, stress is concentrated on the boundary between a portion of the solid electrolyte layer 30 that is in contact with the positive electrode layer 20 and a portion of the solid electrolyte layer 30 that is not in contact with the positive electrode layer 20) due to an impact applied from the outside.
[0042] In order to prevent the above problem, the protective member 40 may be provided on the peripheral portion of the solid electrolyte layer without the positive electrode layer 20 while being interposed between two solid electrolyte layers adjacent to each other with the positive electrode layer 20 interposed therebetween. Figure 1 As shown, the protective member 40 may be disposed between the solid electrolyte layer 32 in the unit cell UC disposed in the second layer L2 and the solid electrolyte layer 31 (L3) in the unit cell UC disposed in the third layer L3, and between the peripheral portion of the solid electrolyte layer 32L2 and the peripheral portion of the solid electrolyte layer 31 (L3). Therefore, the protective member 40 may compensate for the step difference defined by the area difference between the positive electrode layer 20 and the solid electrolyte layer 30.
[0043] Figure 2 It is shown Figure 1 Hereinafter, reference will be made to Figure 2 The protection member 40 according to the present disclosure is described in more detail.
[0044] Reference Figure 2 , the protective member 40 may include a first thermoplastic resin layer 41, a second thermoplastic resin layer 42, and a third thermoplastic resin layer 43 stacked in sequence. Figure 2 As shown, the first thermoplastic resin layer 41 may be provided on the peripheral portion of the solid electrolyte layer 32, and the third thermoplastic resin layer 43 may be provided on the peripheral portion of the solid electrolyte layer 31 (L3). In this case, the second thermoplastic resin layer 42 may be interposed between the first thermoplastic resin layer 41 and the third thermoplastic resin layer 43. In other words, the second thermoplastic resin layer 42 may be provided to space two solid electrolyte layers (for example, see reference numerals 32 and 31 (L3)) adjacent to each other with the positive electrode layer 20 interposed therebetween.
[0045] In this case, each of the glass transition temperature of the first thermoplastic resin layer 41 and the glass transition temperature of the third thermoplastic resin layer 43 may be respectively lower than the glass transition temperature of the second thermoplastic resin layer 42. When the glass transition temperatures of the first to third thermoplastic resin layers 41, 42, and 43 satisfy the above conditions, the protective member 40 may have both excellent impact absorbency derived from the first thermoplastic resin layer 41 and the third thermoplastic resin layer 43 having lower glass transition temperatures and excellent mechanical strength derived from the second thermoplastic resin layer 42 having higher glass transition temperature.
[0046] According to an embodiment, the second thermoplastic resin layer 42 may include various types of well-known thermoplastic resins having a glass transition temperature higher than that of the thermoplastic resins included in the first thermoplastic resin layer 41 and the third thermoplastic resin layer 43. For example, the second thermoplastic resin layer 42 may include at least one selected from the group consisting of polyvinylchloride, polystyrene, polymethyl methacrylate, and acrylonitrile butadiene styrene.
[0047] According to an embodiment, the first thermoplastic resin layer 41 and the third thermoplastic resin layer 43 may each include various types of well-known thermoplastic resins having a glass transition temperature lower than that of the thermoplastic resin included in the second thermoplastic resin layer 42. For example, the first thermoplastic resin layer 41 and the third thermoplastic resin layer 43 may each independently include at least one selected from the group consisting of polyethylene, polypropylene, and ethylenevinyl acetate.
[0048] According to an embodiment, the first thermoplastic resin layer 41 and the third thermoplastic resin layer 43 may include the same type of thermoplastic resin. In this case, the glass transition temperature of the first thermoplastic resin layer 41 may be substantially the same as the glass transition temperature of the third thermoplastic resin layer 43.
[0049] According to an embodiment, the glass transition temperature of the second thermoplastic resin layer 42 may be between 50° C. and 70° C., or preferably, may be 100° C. or higher. In this case, when the glass transition temperature of the second thermoplastic resin layer 42 satisfies this numerical range, the second thermoplastic resin layer 42 may have very excellent mechanical strength.
[0050] According to an embodiment, the ratio of the total thickness of the protective member 40 to the thickness T2 of the second thermoplastic resin layer 42 may be in the range of 1:0.25 to 0.65, in the range of 1:0.30 to 0.60, in the range of 1:0.35 to 0.60, in the range of 1:0.40 to 0.58, or in the range of 1:0.50 to 0.58. In this case, the total thickness of the protective member 40 may be a value obtained by adding the thickness T1, T2 and T3 of each of the first to third thermoplastic resin layers 41, 42 and 43. In some cases, when the thickness T2 of the second thermoplastic resin layer 42 satisfies this numerical range, the second thermoplastic resin layer 42 effectively acts as a support between the solid electrolyte layer (e.g., reference numerals 32 and 31 (L3)), thereby improving the durability and cycle characteristics of the all-solid-state secondary battery.
[0051] According to one embodiment, the ratio of the total thickness of the protective member 40 to the thickness T1 of the first thermoplastic resin layer 41 and the ratio of the total thickness of the protective member 40 to the thickness T3 of the third thermoplastic resin layer 43 may be independently in the range of 1:0.15 to 0.40, 1:0.175 to 0.375, or 1:0.20 to 0.30. In this case, when each of the thickness T1 of the first thermoplastic resin layer 41 and the thickness T3 of the third thermoplastic resin layer 43 independently satisfies the above numerical range, the first thermoplastic resin layer 41 and the third thermoplastic resin layer 43 effectively act as a buffer between the solid electrolyte layers (e.g., reference numerals 32 and 31 (L3)), thereby improving the durability and cycle characteristics of the all-solid-state secondary battery.
[0052] According to an embodiment, the positive electrode layer 20 may include a positive electrode current collector layer 21 and a pair of positive electrode active material layers. In this case, the positive electrode current collector layer 21 may be interposed between the pair of positive electrode active material layers. Figure 2 As shown, the pair of positive active material layers may include a positive active material layer 22 disposed on the bottom surface of the positive current collector layer 21 and a positive active material layer 23 disposed on the top surface of the positive current collector layer 21 .
[0053] According to an embodiment, the negative electrode layer 10 may include a negative electrode current collector layer 11 and a pair of negative electrode active material layers. In this case, the negative electrode current collector layer 11 may be interposed between the pair of negative electrode active material layers. Figure 2 As shown, the pair of negative active material layers may include a negative active material layer 12 disposed on the bottom surface of the negative current collector layer 11 and a negative active material layer 13 disposed on the top surface of the negative current collector layer 11 .
[0054] Method for manufacturing all-solid-state secondary battery
[0055] In the following, reference will be made to Figure 3 and Figure 4 A method of manufacturing an all-solid-state secondary battery according to the present disclosure is described.
[0056] Figure 3 is a view showing a method of manufacturing an all-solid-state secondary battery according to an embodiment of the present disclosure.
[0057] Reference Figure 3 The manufacturing method of the all-solid-state secondary battery according to the present disclosure may include: forming a primary battery stack ST 0 After that, the primary battery stack ST 0 A warm pressing process is performed to form the cell stack ST.
[0058] In this case, the battery stack ST can be compared with the above reference Figure 1 and Figure 2 The battery stack ST described is basically the same, and therefore, a repeated description thereof will be omitted.
[0059] Initial battery stack ST 0 It may be a previous battery stack before the battery stack ST is warm pressed. 0 The battery stack ST may include components substantially the same as those included in the battery stack ST. 0 The stack structure may have a plurality of unit cells UC stacked, and the stack structure may be, for example, a structure having a three-layer structure including a first layer L1, a second layer L2, and a third layer L3, such as Figure 3 shown.
[0060] Can be used to form a primary battery stack ST 0 However, preferably, the protective member 40 is provided on the peripheral portion of the side surface of the solid electrolyte layer 30 having the positive electrode layer 20 where the positive electrode layer 20 is not provided. As described above, a plurality of unit cells UC provided with the protective member 40 are stacked to form a primary battery stack ST. 0 Alternatively, for example, after stacking a plurality of unit cells UC, the protection member 40 may be provided (or inserted) on a peripheral portion where the positive electrode layer 20 is not provided on the side surface of the solid electrolyte layer 30 having the positive electrode layer 20 .
[0061] Therefore, the primary battery stack ST 0 The protection member 40 in the embodiment may be interposed between two solid electrolyte layers (for example, reference numerals 32 and 31 ( L3 )) disposed adjacent to each other with the positive electrode layer 20 interposed therebetween.
[0062] After that, the initial battery stack ST 0 Can be in the initial battery stack ST 0The unit cells UC included in the stack are stacked and warm-pressed in the stacking direction, thereby forming a battery stack ST.
[0063] In this case, the primary battery stack ST 0 Each of the plurality of unit cells UC in the primary battery stack ST can be compressed in the stacking direction. 0 The average thickness of the plurality of unit cells UC in the battery stack ST may be greater than the average thickness of the plurality of unit cells UC in the battery stack ST.
[0064] Similarly, the protective member 40 may be pressed by two solid electrolyte layers (eg, reference numerals 32 and 31 (L3)) disposed adjacent to each other in the stacking direction with the positive electrode layer 20 interposed therebetween. 0 The average thickness of the protection member 40 in the battery stack ST may be greater than the average thickness of the protection member 40 in the battery stack ST.
[0065] In some cases, when the primary battery stack ST 0 When warm pressing is applied to the primary battery stack ST 0 The pressure of each of the plurality of unit cells UC included in the stack may be different from each other. Therefore, when the stack ST is composed of the primary stack ST 0 When forming, the primary battery stack ST 0 Each of the plurality of unit cells UC in the primary battery stack ST may be compressed at a random compression rate. In this case, the primary battery stack ST 0 The plurality of unit cells UC in the battery stack ST may have substantially the same thickness. Alternatively, the plurality of unit cells UC in the battery stack ST compressed at a random compression rate may have different thicknesses from each other.
[0066] Figure 4 Show Figure 3 The protective member 40 in the method for manufacturing the all-solid-state secondary battery according to the present disclosure will be described in more detail.
[0067] In some cases, the components included in the protective member 40 may be the same as those described in reference Figure 2 The components included in the described protection member 40 are substantially the same. Hereinafter, repeated descriptions thereof will be omitted to avoid redundancy.
[0068] According to an embodiment, the glass transition temperature of the second thermoplastic resin layer 42 may be higher than the temperature at which the warm pressing process is performed, and the glass transition temperatures of the first and third thermoplastic resin layers 41 and 43 may be lower than the temperature at which the warm pressing process is performed.
[0069] In this case, during the warm pressing process, the second thermoplastic resin layer 42 having a higher glass transition temperature can serve as a support between two adjacent solid electrolyte layers, and the first thermoplastic resin layer 41 and the third thermoplastic resin layer 43 having a lower glass transition temperature can absorb the impact between the two adjacent solid electrolyte layers. Therefore, the reliability of the warm pressing process can be improved.
[0070] In addition, in the unit cell UC compressed at a random compression rate as described above, the protective member including the first to third thermoplastic resin layers 41, 42 and 43 having a glass transition temperature can absorb the impact between two adjacent solid electrolyte layers or can serve as a support between two adjacent solid electrolyte layers to correspond to the random compression rate.
[0071] According to an embodiment, the thickness T1 of the first to third thermoplastic resin layers 41, 42, and 43 before performing the warm pressing process is 0 、T2 0 and T3 0 It may be greater than the thicknesses T1 , T2 , and T3 of the first to third thermoplastic resin layers 41 , 42 , and 43 after the warm pressing process.
[0072] According to an embodiment, a thickness variation rate of the first thermoplastic resin layer 41 before and after the warm pressing process represented by the following Equation 1 and a thickness variation rate of the third thermoplastic resin layer 43 before and after the warm pressing process operation represented by Equation 3 may be respectively greater than a thickness variation rate of the second thermoplastic resin layer 42 before and after the warm pressing process operation shown in the following Equation 2.
[0073] [Equation 1]
[0074] Thickness change rate of the first thermoplastic resin layer = (T1 0 -T1) / T1 0 ×100[%]
[0075] [Equation 2]
[0076] The thickness change rate of the second thermoplastic resin layer = (T2 0 -T2) / T2 0 ×100[%]
[0077] [Equation 3]
[0078] Thickness change rate of the third thermoplastic resin layer = (T3 0 -T3) / T3 0 ×100[%]
[0079] Hereinafter, the present disclosure will be described in more detail. However, these examples are provided for convenience of explanation, and the scope of the present disclosure is not limited thereto.
[0080] Example 1: Manufacture of an all-solid-state secondary battery including a battery stack and a protective member
[0081] Figure 3 An example primary battery stack structure is shown in . In this case, a stacked structure of a first thermoplastic resin layer (ethylene vinyl acetate; glass transition temperature: -25°C to 0°C), a second thermoplastic resin layer (polystyrene; glass transition temperature: 100°C), and a third thermoplastic resin layer (ethylene vinyl acetate; glass transition temperature: -25°C to 0°C) stacked in sequence is used as a protective member.
[0082] Then, a stacked structure having a heat press process (pressure in the heat press process: 300 to 600 MPa, and a temperature of the heat press process is 90° C.) is manufactured by performing a heat press process on the stacked structure in the stacking direction. Figures 1 to 3 An all-solid-state secondary battery with a battery stack structure as shown.
[0083] In some cases, the negative electrode layer 10, the positive electrode layer 20, and the solid electrolyte layer 30 used to manufacture the all-solid-state secondary battery according to Example 1 include substances described in the following Table 1. In the battery stack structure included in the all-solid-state secondary battery according to Example 1, the thickness of the first thermoplastic resin layer: the thickness of the second thermoplastic resin layer: the thickness of the third thermoplastic resin layer is 25:50:25.
[0084] Table 1
[0085]
[0086] Example 2: Manufacture of an all-solid-state secondary battery including a battery stack and a protective member
[0087] The all-solid-state secondary battery according to Example 2 is manufactured by the same manufacturing process as that of Example 1, except that the ratio of the thickness of the first thermoplastic resin layer: the thickness of the second thermoplastic resin layer: the thickness of the third thermoplastic resin layer included in the protective member of the battery stack in the all-solid-state secondary battery satisfies 40:20:40.
[0088] Example 3: Manufacture of an all-solid-state secondary battery including a battery stack and a protective member
[0089] The all-solid-state secondary battery according to Example 3 is manufactured by the same manufacturing process as that of Example 1, except that the ratio of the thickness of the first thermoplastic resin layer included in the protective member of the battery stack included in the all-solid-state secondary battery: the thickness of the second thermoplastic resin layer: the thickness of the third thermoplastic resin layer satisfies 15:70:15.
[0090] Comparative Example 1: Production of an all-solid-state secondary battery including a battery stack and a protective member
[0091] An all-solid-state secondary battery according to Comparative Example 1 was manufactured by the same manufacturing process as that of Example 1 except that a protective member having a single-layer structure of a first thermoplastic resin layer (ethylene vinyl acetate; glass transition temperature: -25°C to 0°C) was used.
[0092] Experimental Example 1: Evaluation of the reliability of all-solid-state secondary batteries
[0093] Optical microscope (OM) images of the all-solid-state secondary batteries according to Example 1 and Comparative Example 1 were taken, and the results are shown in Figure 5 and Figure 6 middle.
[0094] Reference Figure 5 , it can be seen that the protection member in the all-solid-state secondary battery according to Example 1 is compressed to correspond to the compression rate of the battery stack compressed at a random compression rate generated by the warm pressing process.
[0095] In addition, refer to Figure 6 , it can be seen that the protection member including only the thermoplastic resin having a lower glass transition temperature of the all-solid-state secondary battery according to Comparative Example 1 completely disappears in the warm pressing process performed at a temperature higher than the glass transition temperature.
[0096] Experimental Example 2: Evaluation of Capacity Retention Characteristics of All-Solid State Secondary Batteries
[0097] For the all-solid-state secondary batteries manufactured according to Examples 1 to 3, a plurality of charge / discharge cycles were performed under the conditions of a voltage range of 4.2 V to 2.0 V, a temperature of 50° C., and a rate of 1 / 3C, respectively.
[0098] Reference Figure 7 , it can be seen that the all-solid-state secondary batteries according to Examples 1 to 3 have very excellent capacity retention characteristics. This is because, in the all-solid-state secondary battery, the protective member is disposed in a space without a positive electrode layer between two solid electrolyte layers adjacent to each other with the positive electrode layer interposed therebetween, and flexibly acts as a buffer and a support, thereby improving the reliability of the all-solid-state secondary battery.
[0099] In some cases, it can be seen that the all-solid-state secondary battery according to Example 1 shows the greatest capacity retention characteristics among the all-solid-state secondary batteries according to Examples 1 to 3. This is because the all-solid-state secondary battery according to Example 1 can most effectively exert the function of the buffer member and the function of the support member, thereby contributing to the improvement of the reliability of the all-solid-state secondary battery.
[0100] Experimental Example 3: Evaluation of Coulombic Efficiency of All-Solid-State Secondary Batteries
[0101] For the all-solid-state secondary batteries manufactured according to Examples 1 to 3, multiple charge / discharge cycles were performed under the conditions of a voltage range of 4.2 V to 2.0 V, a temperature of 50° C., and a rate of 1 / 3 C. The coulombic efficiency of the all-solid-state secondary batteries in each cycle was measured, and the results are shown in Figure 8 middle.
[0102] Reference Figure 8 , it can be seen that the all-solid-state secondary batteries according to Examples 1 to 3 have very excellent coulombic efficiency. This is because, in the all-solid-state secondary battery, the protective member is disposed in a space without a positive electrode layer between two solid electrolyte layers adjacent to each other so that the positive electrode layer is interposed therebetween, and flexibly acts as a buffer and a support, thereby improving the reliability of the all-solid-state secondary battery.
[0103] In some cases, it can be seen that the all-solid-state secondary battery according to Example 1 exhibits the greatest coulombic efficiency among the all-solid-state secondary batteries according to Examples 1 to 3. This is because the all-solid-state secondary battery according to Example 1 most effectively exerts the function of the buffer and the function of the support, thereby contributing to the improvement of the reliability of the all-solid-state secondary battery.
[0104] According to the present disclosure, the all-solid-state secondary battery includes a protective member disposed on a peripheral portion of the solid electrolyte layer that does not have a positive electrode layer, between two solid electrolyte layers disposed adjacent to each other so that the positive electrode layer is interposed therebetween. In this case, the protective member can compensate for the step difference defined by the area difference between the positive electrode layer and the solid electrolyte layer. Therefore, the solid electrolyte layer will not break (e.g., crack) during a manufacturing process such as a warm pressing process.
[0105] In some cases, the protective member includes a first thermoplastic resin layer, a second thermoplastic resin layer, and a third thermoplastic resin layer stacked in sequence. Therefore, the protective member can have excellent mechanical strength derived from the second thermoplastic resin layer having a higher glass transition temperature and excellent impact absorption derived from the first thermoplastic resin layer and the third thermoplastic resin layer having a lower glass transition temperature.
[0106] Therefore, in the warm pressing process, the protection member may absorb impact between two solid electrolyte layers adjacent to each other to correspond to a random compression rate, or may support two solid electrolyte layers in a unit cell compressed at a random compression rate.
[0107] Although the present disclosure has been described above with reference to exemplary embodiments and the accompanying drawings, the present disclosure is not limited thereto, but those skilled in the art to which the present disclosure belongs may make various modifications and changes to the present disclosure without departing from the spirit and scope of the present disclosure as claimed in the appended claims.
Claims
1. An all-solid-state secondary battery, comprising: A battery stack, comprising a plurality of stacked unit cells, each unit cell comprising: (i) a negative electrode layer; (ii) a pair of solid electrolyte layers, the negative electrode layer being interposed between the solid electrolyte layers; and (iii) a positive electrode layer, arranged opposite to the negative electrode layer, such that one solid electrolyte layer from the pair of solid electrolyte layers is interposed between the negative electrode layer and the positive electrode layer, and an area of the positive electrode layer facing the one solid electrolyte layer is smaller than an area of the negative electrode layer facing the one solid electrolyte layer; and A protective member, comprising (i) a first thermoplastic resin layer, (ii) a second thermoplastic resin layer and (iii) a third thermoplastic resin layer, wherein the first thermoplastic resin layer, the second thermoplastic resin layer and the third thermoplastic resin layer are sequentially stacked, the protective member is interposed between two adjacent solid electrolyte layers, the positive electrode layer is interposed between the two adjacent solid electrolyte layers, and the protective member is disposed at a peripheral portion of the solid electrolyte layer where the positive electrode layer is not disposed, Wherein, the glass transition temperature of the first thermoplastic resin layer and the glass transition temperature of the third thermoplastic resin layer are lower than the glass transition temperature of the second thermoplastic resin layer.
2. The all-solid-state secondary battery according to claim 1, wherein: The first thermoplastic resin layer and the third thermoplastic resin layer include the same thermoplastic resin.
3. The all-solid-state secondary battery according to claim 1, wherein: The glass transition temperature of the second thermoplastic resin layer is 50°C.
4. The all-solid-state secondary battery according to claim 1, wherein: A ratio of a total thickness of the protection member to a thickness of the second thermoplastic resin layer is 1:0.25 to 0.
65.
5. The all-solid-state secondary battery according to claim 4, wherein: Each of a ratio of a total thickness of the protection member to a thickness of the first thermoplastic resin layer and a ratio of a total thickness of the protection member to a thickness of the third thermoplastic resin layer is 1:0.15 to 0.
40.
6. The all-solid-state secondary battery according to claim 1, wherein: The second thermoplastic resin layer is spaced apart from each of two solid electrolyte layers disposed adjacent to each other with the positive electrode layer interposed therebetween.
7. The all-solid-state secondary battery according to claim 1, wherein: Each of the first thermoplastic resin layer and the third thermoplastic resin layer includes at least one of polyethylene, polypropylene, or ethylene vinyl acetate.
8. The all-solid-state secondary battery according to claim 1, wherein: The second thermoplastic resin layer includes at least one of polyvinyl chloride, polystyrene, polymethyl methacrylate or acrylonitrile butadiene styrene.
9. The all-solid-state secondary battery according to claim 1, wherein: The positive electrode layer comprises: a positive electrode current collector layer; and A pair of positive electrode active material layers, wherein the positive electrode current collector layer is interposed between the positive electrode active material layers.
10. The all-solid-state secondary battery according to claim 1, wherein: The negative electrode layer comprises: a negative electrode current collector layer; and A pair of negative electrode active material layers, wherein the negative electrode current collector layer is interposed between the negative electrode active material layers.
11. The all-solid-state secondary battery according to claim 1, wherein: The plurality of unit cells included in the battery stack have different thicknesses from each other.
12. A method for manufacturing an all-solid-state secondary battery, the method comprising: A primary battery stack is formed by stacking a plurality of unit cells, each unit cell comprising: Negative electrode layer; a pair of solid electrolyte layers, the negative electrode layer being interposed between the solid electrolyte layers; and A positive electrode layer is arranged opposite to the negative electrode layer, so that one solid electrolyte layer from the solid electrolyte layers is between the negative electrode layer and the positive electrode layer, and the area of the positive electrode layer facing the one solid electrolyte layer is smaller than the area of the negative electrode layer facing the one solid electrolyte layer, and a protection member provided in a unit cell, the protection member including a first thermoplastic resin layer, a second thermoplastic resin layer, and a third thermoplastic resin layer, the first thermoplastic resin layer, the second thermoplastic resin layer, and the third thermoplastic resin layer being sequentially stacked in a peripheral portion of one solid electrolyte layer where the positive electrode layer is not provided and on a side surface of the positive electrode layer; and forming a battery stack by performing a warm pressing process on the primary battery stack in a stacking direction of the plurality of unit battery stacks, Wherein, the glass transition temperature of the first thermoplastic resin layer and the glass transition temperature of the third thermoplastic resin layer are lower than the glass transition temperature of the second thermoplastic resin layer.
13. The method according to claim 12, wherein: The glass transition temperature of the second thermoplastic resin layer is higher than the temperature of the warm pressing process, and A glass transition temperature of the first thermoplastic resin layer and a glass transition temperature of the third thermoplastic resin layer are lower than a temperature of the warm pressing process.
14. The method according to claim 12, wherein: In the primary cell stack, the protection member is interposed between two solid electrolyte layers disposed adjacent to each other with the positive electrode layer interposed therebetween.
15. The method according to claim 14, wherein: In the warm pressing process, the protection member is pressed by the two solid electrolyte layers in the stacking direction.
16. The method according to claim 12, wherein: An average thickness of the plurality of unit cells in the primary battery stack is greater than an average thickness of the plurality of unit cells in the battery stack.
17. The method according to claim 12, wherein: The plurality of unit cells in the primary cell stack have the same thickness.
18. The method according to claim 12, wherein: The plurality of unit cells in the battery stack have different thicknesses from each other.
19. The method according to claim 12, wherein: In the battery stack, a ratio of a total thickness of the protection member to a thickness of the second thermoplastic resin layer is 1:0.25 to 0.
65.
20. The method according to claim 19, wherein: In the battery stack, each of a ratio of a total thickness of the protection member to a thickness of the first thermoplastic resin layer and a ratio of a total thickness of the protection member to a thickness of the third thermoplastic resin layer is 1:0.15 to 0.40.
Citation Information
Patent Citations
pPLAⅡγ gene inducing haploid plant and uses thereof
KR1020230139656A